The role of vanadium and pyridine in heteropolycompounds for the selective oxidation of alcohols with hydrogen peroxide - Palermo, Valeria (2013)
This work describes the application of heteropolyacids H3PMo12O40, H4SiMo12O40, H4PMo11VO40, H5PMo10V2O40, H9PMo6V6O40, and a hybrid pyridine-modified heteropolyacid with Keggin structure for the selective oxidation of alcohols to ketones or aldehydes using aqueous hydrogen peroxide and acetonitrile as solvent. The performance of these different catalysts in 1-phenylethanol oxidation was studied. The influence of the reaction temperature, the amount of the catalyst and hydrogen peroxide and the reaction time on the yield of acetophenone was investigated to obtain the optimal reaction conditions. The oxidation ability of the catalyst depended on the number of vanadium atoms present in the Keggin ion and to a lesser extent on pyridine substitution in the Keggin secondary structure. In order to explore the applicability of the method for the selective oxidation of alcohols to ketones or aldehydes, various alcohols were investigated according to the general procedure using the hybrid pyridine-modified heteropolyacid.